Internet of services-based business model: a case study in the livestock industry - Jacqueline Zonichenn Reis; Rodrigo Franco Goncalves; Epaminondas de Souza Lage; Irenilza de Alencar Nääs (Innovation & Management Review, 2022)
Purpose - Considering the relevance of innovative business models in the digitally transformed market and the lack of clarity on the internet of services (IoS) contribution for a business model deployment in current literature, this study aims to fill this gap by evaluating a business model that converges to an IoS adoption in a direct sale of free-range eggs from farmers to consumers. Design/methodology/approach - From the bibliographical research regarding the IoS and business model, the authors developed an IoS-based model framework. The framework has been evaluated in a real business scenario by using a single case study through an interview with the entrepreneur and documental analysis. Findings - As the main result, a framework with the attributes can be considered a tool for an IoS-based business model deployment. The case study concluded that the business is aligned with the IoS adoption, and the framework presents adherence to it. Research limitations/implications - The case study was limited to only one company owing to the IoS's novelty and the lack of correlated business models. Although the case study limits to the agriculture field, the proposed framework may be broadly applied. Originality/value - Considering that the lack of a comprehensive business model causes new businesses to face challenges, it is relevant bringing up the present case study of the IoS-based business model, which correlates these two subjects, still poorly explored in the scientific literature: IoS and business models.
Keywords: 650; Agriculture 4.0; Business model; Digital transformation; Internet of services